1989
DOI: 10.1080/00224545.1989.9712062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prolonged Deprivation on Attributional Style

Abstract: The effects of prolonged deprivation and outcome on attributional style were examined in a 2 x 2 factorial design with two levels of deprivation (high and low) and two levels of outcome (good and bad). Indian subjects (N = 80) were selected on the basis of extreme scores on a prolonged deprivation scale; they provided an attributional style scale of good and bad outcome situations. High-deprived subjects attributed bad outcomes to more internal, stable, and global causes compared with low-deprived subjects. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…These negative expectations are very naturally termed "pessimism," but unlike the pessimistic attributional style of the Hopelessness Theory of Depression, they are an enduring trait, present in good times and bad, rather than interpretations attached to a negative event. Only three studies have assessed SES and attributional style, all in adolescents, two using a single negative event to assess pessimism (Jain & Mal, 1984;Mal et al, 1990) and one using the attributional style questionnaire (Singh & Nathawat, 1989). These studies operationalized SES as a difference in degree of material deprivation in rural India.…”
Section: Introductionmentioning
confidence: 99%
“…These negative expectations are very naturally termed "pessimism," but unlike the pessimistic attributional style of the Hopelessness Theory of Depression, they are an enduring trait, present in good times and bad, rather than interpretations attached to a negative event. Only three studies have assessed SES and attributional style, all in adolescents, two using a single negative event to assess pessimism (Jain & Mal, 1984;Mal et al, 1990) and one using the attributional style questionnaire (Singh & Nathawat, 1989). These studies operationalized SES as a difference in degree of material deprivation in rural India.…”
Section: Introductionmentioning
confidence: 99%
“…The first study, with adolescent boys, found that those suffering greater deprivation were more likely to attribute their failure on a task to internal (their ability or effort) rather than external (luck) factors 13 . A later study demonstrated that low SES adolescent boys showed more pessimistic attributional style for bad outcomes than low-deprived subjects, but no differences in attributing good outcomes using the scale Seligman and colleagues developed (Children's Attributional Style Questionnaire 14 ) 15 . Another study found that low SES adolescents (both genders) were more…”
mentioning
confidence: 98%